Leaving Town for the Market: The Emergence and Expansion of Social Trust in the Works of Elinor Ostrom and Henry Sumner Maine - Goëtzmann, Marc (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
This paper uses the evolutionary frame provided by the Victorian jurist Henry Sumner Maine to describe the process by which trust can be seen as the product of a gradual development that starts with small-scale communities and later allows market exchanges to develop themselves. I also argue, using the work of Elinor Ostrom (1990), that trust emerges first within small-scale communities, where first- and second-degree collective action problems need to be resolved. The development of a social disposition to trust is closely linked with an institutional context that encourages individuals to take the externalities of their actions into account. This is made possible by customary mechanisms, as the development of social trust at this stage cannot rely on a mighty “Leviathan”. Therefore, this paper questions the claim that social trust is the product of market exchanges. Market exchanges might favor the further growth of social trust, hands in hands with the right institutional frame. However, this growth is not just the transposition of a previously acquired disposition to trust. The work of Henry Sumner Maine interestingly underlines the importance of the co-development of institutions and trust, from its origin in small communities to its expansion to market exchanges. Both Ostrom’s and Maine’s perspectives underline the fact that trust and trustworthiness are complementary and question a-rational perspectives on trust. This paper also elaborates on the claim, coming from the literature on contract law, that focusing on sanctioning mechanisms can be highly counterproductive. Keywords: Trust; Markets; Henry Sumner Maine; Contract Law; Customary Law; Ostrom Index: Introduction – Markets and layers of trust – Trust as an institutional product for cooperation – Trust, markets and contract law in Henry Sumner Maine’s work – Some conclusions – References